Simulation of a UAV-based wireless sensor network on NS-3 to analyze IEEE 802.11 performance - Mr. Akshit Lamba, Mr. Gaurav Tamrakar, Mr. Honey Gaur (Mathematical Statistician and Engineering Applications, 2022)
Mechanical Winged Vehicle (UAV) can probably change the future detached sensor institution (WSN). Ultimate active, elite exhibition, important and smartest news variety are accomplished in WSN through the UAV on account of UAV gives an strength-able temporary agreement with excellent chance. Still, UAV-located WSN exhibitions are affected by miscellaneous foundation frontiers. To analyze this issue, it is main to investigations the impacts of foundation perimeters on the UAV-located WSN killing. In this paper, we plan a NS-3 content for UAV-located WSN as per the growing habit of TCP/IP model. We organize all coatings by utilizing NS-3 model parts and set and regulate the values exploited by objects to examine the impacts of foundation perimeters (approach structure, UAV management design, UAV speed, number of sensors, and sensor traffic age rate) on throughput, and normal respite. The duplication results show that the RTS/Repetitive stress injury approach instrument gives favorite killing over the fundamental news approach system and the ability to move model that has happened urged shows better killing than the arbitrary flexibility model. Also, the effects show that greater speed of UAV debases the framework killing accompanying greeting to throughput and respite. Our plan arrangement addresses a decent rule for new NS-3 customers to plan and change content and results remarkably benefit the arrangement plan and the board.